Characterization of C9orf72 haplotypes to evaluate the effects of normal and pathological variations on its expression and splicing. - Israel Ben-Dor; Crystal Pacut; Yuval Nevo; Eva L Feldman; Benjamin E Reubinoff (PLoS Genetics)
Expansion of the hexanucleotide repeat (HR) in the first intron of the C9orf72 gene is the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) in Caucasians. All C9orf72-ALS/FTD patients share a common risk (R) haplotype. To study C9orf72 expression and splicing from the mutant R allele compared to the complementary normal allele in ALS/FTD patients, we initially created a detailed molecular map of the single nucleotide polymorphism (SNP) signature and the HR length of the various C9orf72 haplotypes in Caucasians. We leveraged this map to determine the allelic origin of transcripts per patient, and decipher the effects of pathological and normal HR lengths on C9orf72 expression and splicing. In C9orf72 ALS patients' cells, the HR expanded allele, compared to non-R allele, was associated with decreased levels of a downstream initiated transcript variant and increased levels of transcripts initiated upstream of the HR. HR expanded R alleles correlated with high levels of unspliced intron 1 and activation of cryptic donor splice sites along intron 1. Retention of intron 1 was associated with sequential intron 2 retention. The SNP signature of C9orf72 haplotypes described here enables allele-specific analysis of transcriptional products and may pave the way to allele-specific therapeutic strategies.